Between naturalistic and theatrical: Contrast narratives as context-based space explorations - Luthfia Hananti; Resza Riskiyanto (ARSNET, 2023)
The study explores contrasting narratives and the intersections between them as the basis of context-based space exploration. Narrative approaches demonstrate possibilities of creatively expanding the design process with its values on imagination and storytelling. Yet, with the focus of stories as the basis of narrative exploration, discussion about its relation to context is often limited. This study introduces the exploration of contrast narratives by exploring the intersection between the naturalistic and theatrical conception of space presented in Tim Burton's 1990 film titled Edward Scissorhands. The close relation of a film to imagination provides possibilities for a more rich and extensive spatial design. The results of this study demonstrate the contrast narratives depicted by differing colours, proportions, and conditions of space throughout the film. Intersections between narratives exist through interactions between characters that are repositioned from one narrative to the other, highlighting how users coming from contrasting contexts may adapt and appropriate new spaces in time. The idea of contrast reveals the contextual relations between narrative, space, and time, demonstrating a potential basis for developing a context-based architectural design method.